PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V DI SD MUHAMMADIYAH 5 - Nopiana, Silvia; Jenal Mutaqin, Ejen (Bale Aksara, 2020)
This research is motivated by the low learning motivation of the students influenced by the weak implementation of the learning process at schools. Starting with the description above, the problem in this study is "Is there the influence of the Student Facilitator and Explaining (SFAE) learning model for student learning motivation to science subjects in 5th grade of SD Muhammadiyah 5?". Then, the purpose of this study is to determine the effect of the Student Facilitator and Explaining (SFAE) learning model on students' learning motivation to science subjects in 5th grade of SD Muhammadiyah 5. The method used in this study is a quasi-experimental method with the Nonequivalent research Control Group Design as the research design. The data of this study is obtained by providing a pretest and posttest questionnaire. The population of this study are all fifth grade students of SD Muhammadiyah 5. Then, the sample of this study is VA class students amount of 25 students and VB class students amount of 25 students. Based on the results of the parametric statistical tests using the t-test, significance value is obtained (sig.2-tailed) in amount of 0.001 which means smaller than 0.05 (0.001 < 0.05) with the decision that H0 is rejected and Ha is accepted. Based on this analysis, it can be concluded that Student Facilitator and Explaining (SFAE) learning model has a significant effect on student learning motivation to science subjects in 5th grade of SD Muhammadiyah 5.